Preliminary Analysis Of Using Game in Problem Based Learning in Learning Mathematic - Shahbodin, F.; zareena, rosli (2011)
The growing awareness of mathematic competency in education and careers has been as an important agenda among parents and students nowadays. Thus, teaching mathematic effectively is a challenge to educators in schools and higher institution. The combination of Problem Based Learning method and game in mathematic environment can be synchronizing to help students mastering mathematic knowledge heuristically. The objective of this paper is to highlight the literature review and the preliminary analysis done in the early phase of the research of Using Game in Problem Based Learning in Learning Mathematic. The paper also will discuss on the research framework that is divided into 3 parts; control mode, development and testing